(3GdYhGed GdeGFIs - (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
q (3hHYO aEf GdYhGed ai GdfMh Ydi eG Cdag GdTjN YHO GdbGgQ Hf YHO GdQMef GdLQLGfi QMeI Gddg Ydjg eGFI YGed hgj JfbSe Edi bSejf s
(3BNQgG (B:s
(3agPg eGFI YGed adG jSJZfi GdUZjQ hGdcHjQ hGdQajY hGdhVjY Yf eYQaJgG hGSJYeGdgG hGddg Gdehab ddUhGH hEdjg GdeQLY hGdeBH hGddg CYde s
(3Vef eLehY , JQJjHgG (B: 2s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B606s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1179s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs